The art of aging well: a study of the relationship between recreational arts engagement, general health and mental wellbeing in cohort of Australian older adults - Davies, Christina R.; Budgeon, Charley A.; Murray, Kevin; Hunter, Michael; Knuiman, Matthew (Frontiers in Public Health, 2023)
Introduction Evidence of the benefits of arts engagement to community wellbeing has been mounting since the 1990s. However, large scale, quantitative, epidemiological studies of the “arts–healthy aging” relationship, or the types of arts older adults voluntarily choose to engage in as part of their everyday life, for enjoyment, entertainment or as a hobby (vs. therapy or interventions) are limited. The aims of this study were to describe older adult recreational arts engagement via the Busselton Healthy Ageing Study (BHAS) cohort, and to determine if there was an association between arts engagement, general health and mental wellbeing. Methods Overall, 2,843 older adults (born 1946–1964) from the BHAS cohort (n = 5,107) who had completed a supplementary arts survey (n = 3,055, 60%) and had data on required variables were included in this study (93% of those eligible). The dependent variable was general health (SF12) and subjective mental wellbeing (Warwick-Edinburgh Mental Wellbeing Scale, WEMWBS). The independent variable was hours engaged in recreational arts in the last 12 months. A descriptive analysis followed by a linear regression analysis was conducted. Results The prevalence of recreational arts engagement in the last 12 months was 85% (mean = 132 h/year). Older adults engaged in the arts in a number of ways including attending events (79%), actively participating/making art (40%), as an arts society/club/organization member (20%), by learning about the arts (13%) or by volunteering/working in the arts (non-professional, 11%). When general health was assessed via the SF12, the average physical component score (PCS) was 50.1 (SD 8.9) and the average mental component score (MCS) was 53.6 (SD 8.3). When mental wellbeing was assessed, the average WEMWBS score was 54.9 (SD = 8.6). After adjustment for 12 demographic and lifestyle covariates, it was found that older adults who engaged in any recreational arts in the last 12 months had significantly higher WEMWBS scores and higher SF12 physical component scores than those who did not engage in the arts (0 h/year). Discussion Evidence of an arts-health relationship was found in this study. The suitability of the arts as a population based, healthy aging strategy to influence the mental wellbeing and general health of older adults should be investigated further.